Predation of Juvenile Japanese Sea Cucumber Apostichopus japonicus by Kelp Crab Pugettia ferox - Inaba, Nobuharu; Matsumoto, Takuma; Kawai, Hiroshi; Anaguchi, Yuji; Matsuno, Kohei (Frontiers in Marine Science, 2021)
The predation of commercially important Japanese sea cucumber Apostichopus japonicus by the kelp crab Pugettia ferox, widely distributed in coastal northeast Asia, was examined in field sampling and laboratory experiments. The ossicles of A. japonicus were detected from the stomach contents of a natural population of P. ferox at the rate of 32.4% of 68 individuals collected within artificial intermediate sea cucumber reefs for releasing hatchery-produced juveniles in December 2018. In the following laboratory experiments, a high mortality rate (7.7±2.4 individuals day-1) of juvenile A. japonicus (15.35±2.47 mm) was observed despite the different sizes and sex of P. ferox tested. It was also confirmed that a maximum of five sea cucumbers were killed and cut into small pieces within the first two hours. Smaller and younger P. ferox individuals (adolescent) between carapace widths of 14.2 to 17.8 mm actively decorated themselves using pieces of chopped sea cucumber after feeding. Attached pieces of sea cucumber were observed to be fully eaten within a week, suggesting a possible strategy by P. ferox of short-term food storage as well as mimicry. This study demonstrates considerable evidence that predation mortality by sufficiently mobile P. ferox on commercially important A. japonicus can be significant, causing high mortality at the early life stage in the natural environment, especially in areas releasing hatchery-produced juveniles. It is also worth noting that the utilization of freshly chopped sea cucumbers as decoration material and food storage is a unique and novel ecological trait of P. ferox.